2012
DOI: 10.1002/rcm.6420
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profiling for early diagnosis and progression of colorectal cancer using direct‐infusion electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry

Abstract: Our study revealed that the consideration of CRC stages would be necessary in diagnostic biomarker discovery, as well as that attention should be paid to the facile loss of methyl chloride from the [M + Cl](-) form of LPC(16:0) in its tandem mass spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 34 publications
1
71
0
1
Order By: Relevance
“…In this review, there was evidence that metabolite modulation was discernable at very early stages of GI cancer (30,46,52,(57)(58)(59). Several studies reported incremental metabolomic changes with invasive (41,43,58,59) and metastatic (46,70,71) progression. In addition, three studies in colorectal cancer that were excluded from the appraisal process owing to their design nonetheless demonstrated pertinent findings to metabolomic dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, there was evidence that metabolite modulation was discernable at very early stages of GI cancer (30,46,52,(57)(58)(59). Several studies reported incremental metabolomic changes with invasive (41,43,58,59) and metastatic (46,70,71) progression. In addition, three studies in colorectal cancer that were excluded from the appraisal process owing to their design nonetheless demonstrated pertinent findings to metabolomic dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies investigated esophageal cancer (39-47), 3 gastric cancer (48)(49)(50), and 15 colorectal cancer (29,30,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). Two studies investigated more than one GI malignancy (64,65).…”
Section: Resultsmentioning
confidence: 99%
“…Some of these substances, including hexadecanedioic, octadecanoic, eicosatrienoic, and myristic acids, belong to a panel that could be used to discriminate early-stage CRC patients from healthy controls. However, the authors highlighted that further studies are required to confirm the changes in the levels of these lipids with CRC progression and to determine why these alterations occur [19]. De novo lipid synthesis and lipid metabolism are strongly regulated in cancer tissues through oncogene activation [20].…”
Section: Introductionmentioning
confidence: 95%
“…This hybrid quadrupole-Orbitrap-ion trap mass spectrometer is equipped with three mass analyzers, two detectors, and two collision cells enabling complementary multi-stage fragmentation analysis using both quadrupole-based higher-energy collisional dissociation (HCD) and ion trap-based resonant-excitation collision-induced dissociation (CID). The ultra-high-field mass analyzer of the Orbitrap Fusion affords acquisition of FTMS spectra with resolving power up to 450,000 (full width at half maximum (FWHM) at m/z 200) at a transient duration of 1 s. The high resolving power at this scan speed is thus far unsurpassed by any other commercially available Orbitrap instrument, and at m/z 400 comparable to that of commonly used FT-ICR mass spectrometers operated with a transient duration of 1 s, as typically used for routine analysis [17,[25][26][27]. A key benefit of high resolving power for lipidomic analysis is the ability to accurately discriminate lipid species with isobaric nominal masses as well as their isotopes and, hence, support accurate lipid identification [17,28].…”
mentioning
confidence: 99%